REGISTER BURUH KELAPA KOPRA DI DESA PULAU KUMBANG KABUPATEN KAYONG UTARA: KAJIAN SOSIOLINGUISTIK - Alma, Safariani; Patriantoro, Patriantoro; Jupitasari, Mellisa (Universitas Tanjungpura, 2025)
This study aims to analyze the types of registers and register functions used by copra coconut workers in Pulau Kumbang Village, North Kayong Regency using sociolinguistic studies. The method used in this research is descriptive method with qualitative form. The data sources in this research are laborers who work in copra coconut processing in Pulau Kumbang Village, North Kayong Regency. Data collection techniques in this research used observation, interview, free listening, note taking, and recording. Based on the results of the research, 23 registers of copra coconut laborers were found with details of 4 types of limited scoping registers and 19 types of open scoping registers. The register functions found in this study are 11 instrumental functions, 6 regulatory functions, 3 representational functions, 4 interactional functions, 2 personal functions, and 6 heuristic functions. This research also produces teaching modules on Descriptive Text material for class VII Junior High School Phase D of the Merdeka Curriculum.